AB0470 Responsiveness of systemic lupus erythematosus patients after rituximab treatment: a single center experience. (15th June 2017) - Tsao, YP; Tsai, CY
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex disease with multi-organ presentations. Lupus nephritis, which results from autoantibody deposition at glomerulus, induces inflammation and damage. Lupus nephritis is also the leading cause of comorbidity in SLE patient and associated with poor prognosis. Objectives: To evaluate the treatment responsiveness of rituximab in patients with SLE. Methods: Patients should fulfill the criteria of 1997 American College of Rheumatology classification criteria for SLE. Patients underwent chemotherapy, with severe infection, under hemodialysis or after kidney transplantation were excluded. Total 37 patients were evaluated receiving rituximab infusion from 2009 to 2013. Clinical parameters were measured before and after rituximab usage. Results: Among the 37 patients, the female patient was 89.2%. Mean age was 39.53 years old. The mean creatinine level remained similar during the 36 months of follow-up. In the beginning of the treatment, the mean creatinine level was 1.40mg/dl (SD 0.84). After 12, 24, 36 months of follow-up, the mean creatinine levels were 1.73mg/dl, 2.16mg/dl, and 2.40mg/dl, respectively (p=0.431, 0.148, 0.328). The mean proteinuria level was 3.51g/day initially (SD 2.52), but it rapidly decreased to 1.60g/dl after 6 months of follow-up (p<0.001), and further decreased to 1.40g/day, 1.12g/day, and 0.90g/day after 12, 24, 36 months of follow-up (p=0.001, 0.002, 0.012). The mean ds-DNA level was 216IU/ml in the starting of the treatment, and it decreased to 97.04IU/ml, 88.28IU/ml, 94.6IU/ml after 12, 24, 36 months of follow-up (p=0.002, 0.003, 0.05). The C3 level revealed elevation after 36 months of follow-up. The mean C3 level was 70.63mg/dl initially, and increased to 88.60mg/dl, 90.65mg/dl, and 96.20mg/dl after 12, 24, 36 months of follow-up (p<0.001, 0.002, 0.011). The platelet level remained similar from the beginning of the study to 36 months of follow-up (269.97K/cumm to 253.5K/cumm, p=0.929). The improvement of proteinuria was significant and could be detected in 6 months, which had significant correlations with the reduction level in 24 months (p<0.001). This suggested that early improvement of proteinuria may predict the further responsiveness. Conclusions: Although the role of rituximab still remained controversial in the treatment of systemic lupus erythematosus, it showed positive effects in our single center's experience. Early response to rituximab was an important predictor of further sustained responsiveness and reduction of proteinuria and other clinical parameters. Disclosure of Interest: None declared